Tes Buta Warna Berbasis Komputer - Maria Widyastuti; Suyanto Suyanto; Fazmah Arif Yulianto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Color blindness is a condition where someone could not see the difference betweentwo colors or more. There are some color blindness classifications, and so there exist somemethods to test whether or not someone has color-blind symptom (and if so, in whatclassification). Ishihara test is a standard and simple world wide-known and used test.Ishihara used 38 pages filled with multicolored dots which some of them resembles numbersor colored-path.There are two most important disadvantages of using Ishihara test tool. First, the tool(book) is not easy to find (or buy), so anyone who wants to take the test usually go to thedoctor or some eye-specialist clinics. Second, the images shown in the book were static. Itmeans we can cheat the test by memorizing each number(s) appeared on every page.Computer-based test can solve those two problems. The application has beenevaluated and tested in Rumah Sakit Mata Cicendo Bandung. The result shows, that thisparticular application can classify up to eight color-blind types (protanopia, deuteranopia,weak protanomali, weak deuteranomali, strong protanomali, strong deuteranomali, and bothmonochromat complete color blindnesses).Keywords: color blind, Ishihara test